LITHUANIA IN THE EU BUDGET REVIEW PROCESS: BETWEEN EUROPEAN AND NATIONAL INTERESTS - Ibenskas, Raimondas; Brožaitis, Haroldas (Politologija, 2015)
National interests, traditionally expressed in terms of net balances, dominated the negotiations on the financial framework of the European Union for 2007–2013 and were crucial in determining only incremental reforms of the EU budget. Although the strategy based on maximising EU financial support enables Lithuania to receive significant financial allocations from the EU budget in 2007–2013, its size is expected to decrease during the period of next financial framework. In addition, the EU budget programmes unfit to the Lithuanian contexts might have negative repercussions to the economy of the country. These problems determine the necessity to discuss a different strategy for the EU budget review in 2008–2009 and the negotiations on next financial framework.In this article we raise a hypothesis that a more beneficial strategy for Lithuania would be to support EU policies and programmes which would bring the added value to the whole EU while also stressing the specific Lithuanian interests related to these policies and programmes. The conceptual framework used to check the hypothesis consists of two stages. First, the objectives of the EU budget and major tools to implement them were indicated drawing from provisions of the EU Treaties (in line with the changes introduced by the Lisbon Reform Treaty), preferences of EU citizens, the fiscal federalism theory and evaluations of EU policies and programmes. Second, the economic, social and political impact of the EU budget (reformed in the way described in the first stage of the analysis) on Lithuania was analysed.The findings of the article provide indefinite but clear support to the hypothesis. According to the political and economic criteria indicated above, the Common Agricultural Policy should seek to implement two goals, namely, increasing competitiveness of the EU agricultural sector and providing public goods (environment, landscape, animal welfare etc.). Such a reform would be more beneficial to Lithuania in comparison to the current policy, however, a specific interest of Lithuania is to assure that it is accompanied by strong rural development policy, which would assure financial support to rural areas during the period of re-structuring of the agricultural sector.The Cohesion policy should also be radically reformed by concentrating financial support only to the least developed regions and countries of the EU and making its connection to the objectives of the Lisbon Strategy looser. Again, such a reform would be beneficial to Lithuania, because it would allow putting the cohesion support more in line with national investment needs and priorities and enable developing national planning capacities.Finally, the funds saved as a consequence of the reforms of the CAP and Cohesion Policy should be allocated to four groups of priorities, namely, Lisbon Strategy goals, energy, climate change and environment, justice, liberty and security and external relations. Such re-allocation would serve Lithuanian interests well, provided that its specific interests – adequate funding to trans-European transport and energy infrastructure, external border protection and European Neighbourhood and Partnership Instrument as well as research and development programmes (including temporary preferential treatment of less developed Member States) – would be taken into consideration.In addition to the major objective of the article, the positions of other Member States as regards EU budget expenses and the impact of the own resources system on Lithuania were also examined in the article.The analysis of other Member States’ positions on the EU budget resulted in rather mixed prospects for the reform described above. On the one hand, virtually all Member States support more funding for new priorities falling in the four categories indicated in this article. On the other hand, only a handful Member States endorse a necessary step into this direction – the reduction in the funding levels of the CAP and Cohesion policy. In the context of very unlikely increase in the total EU budget expenditure due to net payers’ resistance, it is still to be seen whether the remaining Member States will decide to support the EU budget which promotes the objectives beneficial to the whole EU or they will remain strongly bound to their national interests on this issue.As concerns the impact of the own resources system on Lithuania, it is concluded that the introduction of the EU tax would not benefit Lithuania and the EU, because financial contributions from the Member States would vary a lot. However, the VAT resources and all corrections and rebates should be abolished.